Genetic transformation with cell wall-associated deoxyribonucleic acid in Bacillus subtilis. - Doyle, R J (1980)
Cell walls from bacillus subtilis 168 were prepared by conventional methods and found to contain deoxyribonucleic acid (DNA). In transformation assays, after autolysis, it was found that two major regions of the chromosome were selectively enriched in the wall preparations. One region clustered around the replication origin and is represented by the markers purA16, ts8132, thiC5, sacA321, and hisA1. The other region included the replication terminus with representative loci metB10, citK5, gltA292, and pyrA1. All other (internal) loci which were examined showed no statistical enrichment. The two areas of enrichment were similar to but more extensive than those reported for membrane-DNA complexes. The wall preparations also contained protein and lipid, indicating a possible membrane involvement. Analyses of the cell walls revealed that the fatty acid composition of the membrane component was not typical of the for B. subtilis protoplast membranes or for lipoteichoic acids. In addition, radioiodination of cell wall autolysates, followed by gel electrophoresis and autoradiography, demonstrated the presence of proteins not readily detectable in bulk protoplast membranes or on the surfaces of intact cells. These data suggest that a unique component of the membrane and regions of the B. subtilis genome involved in DNA replication events are tightly associated with cell walls. The binding of DNA-membrane complexes to the "rigid" cell wall and the replication of the wall could be a mechanism by which the segregation of growing chromosomes occurs.